Age-related and sex-specific trends in sleep quality in children and adolescents - Hugi Hilmisson; Solveig Dora Magnusdottir; Robert Joseph Thomas (Frontiers in Neuroscience, 2025)
IntroductionStrong developmental trends are well described in non-rapid eye movement (NREM) sleep characteristics but also seen in cyclic-alternating-pattern (CAP). The latter shows a bimodal distribution: slow wave dominant (A1) complexes early in life and A2/A3 complexes later in life. This analysis aimed to assess trends in CAP-linked cardiopulmonary coupling (CPC) calculated Sleep Quality Index (SQI) from childhood through adolescence.MethodsAnalysis of de-identified data from the SleepImage® System (MyCardio LLC, Denver, CO, United States), using CPC-calculations evaluating integrated electrocortical-autonomic-respiratory interactions to derive sleep states, SQI, and combined with oxygen saturation, an apnea hypopnea index (AHI).ResultsForty-one thousand nights of continuous sleep recordings of ≥ 6 h in duration and ≥ 4 h of total sleep time (TST), with good signal quality (≥ 80%) from individuals < 18 years of age were included in the analysis (48% girls-52% boys). Age groups were defined as 2–5 years (preschool-age, 39% girls-61% boys), 6–9 years (school-age, 47% girls-53% boys), 10–13 years (early-adolescent, 47% girls-53% boys), 14–17 years (late-adolescent, 52% girls-48% boys). In the cohort 20% had moderate- (AHI3% 5–10) and 8% severe sleep apnea (AHI3% ≥ 10). SQI is highest in school-aged children that are expected to sleep for 9–12/24 h with no sex differences observed (75.8 ± 15.8 and 75.3 ± 16.2; p = 0.06). Preschool-aged children are expected to sleep for 10–13/24 h, have a slightly lower SQI compared to school-aged children, with SQI higher in girls (73.4 ± 17.5 and 71.6 ± 19.2; p < 0.001). During early adolescence, when sleep duration is expected to be 8–10/24 h, SQI is significantly lower in girls compared to boys (70.5 ± 17.4 and 71.8 ± 17.0; p < 0.001). In late adolescence, SQI decline continues, but at a slower rate in girls who, at this age, girls have higher SQI than boys (63.1 ± 18.3 and 60.5 ± 18.2); p < 0:001. AHI3% is significantly lower in girls in all age-groups; it is lowest in school-age children and gradually increases during adolescence.ConclusionChildren seem to reach their full potential in sleep stability and quality around school-age. In early adolescence, measured sleep stability and quality start to gradually decline, with the decline starting earlier in girls while larger in boys during the adolescent years.